Effects of Histoplasma capsulatum on murine macrophage functions: inhibition of macrophage priming, oxidative burst, and antifungal activities. - Wolf, J E (1989)
Histoplasma capsulatum yeast cells fail to trigger an oxidative burst response in normal murine macrophages. The results of this study, in which an in vitro assay of macrophage antifungal effects was used, extend these findings. During 18 h of incubation, unprimed elicited murine macrophages inhibited H. capsulatum growth only when macrophages were present in great excess. Gamma interferon (IFN-gamma)-primed macrophages showed enhanced fungal growth inhibition but a similar requirement for an excess of phagocytes. Macrophages containing heat-killed H. capsulatum exhibited diminished antifungal effects toward viable H. capsulatum and Saccharomyces cerevisiae cells. Parallel experiments showed no comparable effect of ingested latex particles on macrophage antifungal activity. Using chemiluminescence as a measure of the oxidative burst, we found that macrophages primed in vitro with IFN-gamma alone failed to exhibit a significant response to triggering by H. capsulatum yeast cells unless a second priming agent (tumor necrosis factor alpha or bacterial lipopolysaccharide) was added to IFN-gamma. Furthermore, macrophage priming with single agents was blocked by the prior ingestion of heat-killed H. capsulatum. These studies provide evidence that ingestion of H. capsulatum yeast cells can induce a prompt and enduring deactivation of murine macrophages.